If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 4q = 12 Solving 2p + 4q = 12 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4q' to each side of the equation. 2p + 4q + -4q = 12 + -4q Combine like terms: 4q + -4q = 0 2p + 0 = 12 + -4q 2p = 12 + -4q Divide each side by '2'. p = 6 + -2q Simplifying p = 6 + -2q
| 3x^2+12x=1 | | 2g^2-35g+17= | | 4x^2-16x+7= | | m^2-7m-18= | | 8m^3+14m^2-20= | | 5x+8y=55 | | -27+13= | | x-(-2)=-20 | | 21=4-r | | (7*x)-(3*y)-(4*x)-(2*y)= | | 6v^2-144+12v=0 | | 7x-3y-4x-2y= | | 4+3(x+9)=12 | | R^2+7n=-6 | | 2-4(x+1)=4-3x | | 3(x+1)-2x=4-3x | | x/6+3=x-1/2 | | 9(4-2x)+10=4+6(3x-5) | | 1.5=x+4.4 | | N^2+2-3n=0 | | -4.5y=36 | | -11+t=-20 | | 1.5w-16=8 | | 7-8x=13x+11+x | | -1/6+z=-1/11 | | 1/6+z=-1/11 | | (9t+4)(5t-15)=0 | | (2x+4)=(3x+8) | | -135=-9n | | 5(3t-5)=6(2t+3) | | -1/3+2x=-5/6 | | 3/2x-19=18 |